The business potential of Arctic Berry Wax as an ingredient in natural cosmetics : Case study of wax purchasing exhibitors at the Trade Fair Biofach Vivaness 2018 - Schromm, Eva-Maria (Oulun ammattikorkeakoulu, 2018)
This research aims at determining the commercial potential of Arctic Berry Wax within the Natural Cosmetics industry from the viewpoint of wax purchasing professionals. For researching within a real-life context, the case study method has been chosen. This thesis is commissioned by the multidisciplinary wax project, which is an Interreg funded joint project of Northern Universities to examine the properties as well as the commercial potential of Arctic Berry Wax within different industries. Arctic Berry Wax is currently a sidestream of the Northern food industry that is not commercially used. The focus of this study are professional buyers in the Natural Cosmetics industry, the objective is to establish if Arctic Berry Wax could be considered as an alternative ingredient evaluated by purchasing professionals. A case study allows the use of multiple sources and is situated in a real-life context. This case study uses desk research and empirical data. The largest business to business Trade Fair in the Natural and Organic Food and Cosmetic industry, the Biofach-Vivaness 2018, has been visited for data gathering. Qualitative data was gathered by conducting theme interviews among professional buyers at the Biofach-Vivaness Trade Fair 2018. The newest trends and controversies in the industry were presented at the adjacent Vivaness Congress. Moreover, desk research was conducted to find background information on waxes. It has been established that there is a general interest among buyers for alternative ingredients. The findings indicate that from a buyer’s viewpoint, it is necessary to approve the Arctic Berry Wax for usage in cosmetics, develop the raw material into a product by providing data, technical details as well as possible proof of origin or certification to the buyer along with the wax. This includes the creation of a marketing story. Furthermore, the name Arctic Berry Wax should be reviewed, if it creates a realistic image among buyers and consumers. Greenwashing is a very sensitive topic in the Natural ...